Class Size, Education, and Wages - Christian Dustmann; Najma Rajah; Arthur van Soest (Institute for the Study of Labor (IZA), 2002)
This paper examines the effects of class size on the decision to stay on in full time schooling at the age of 16 and on wages at later stages in life. Little research exists on the effect of school quality on career decisions, although it has potentially important long term implications. We use micro data for England and Wales that contain an unusually rich set of variables on parental background and previous achievements. We find that class size, measured as the pupil-teacher ratio at the school level, has a sizeable and significant effect on the decision to remain in full time education beyond the minimum age. This finding is very robust and persists when school type variables, exam results, and results from past ability tests are controlled for. We also estimate wage equations including the staying on decision at age 16 as one of the explanatory variables. The effect of staying on is significantly positive for wages at age 33 and age 42, and for females also at age 23. Combining this effect with the effect of class size on the staying on decision, our results reveal that class size significantly affects future wages. Reduced form models in which wages are directly regressed on class size lead to much less accurate and generally insignificant estimates.
Keywords: J24; I20; C35; 330; school inputs; educational attainment; training; Allgemeinbildende Schule; Bildungsniveau; Lohnniveau; Statistischer Test; Bildungsertrag; England; Wales; Klassengrösse